2014
DOI: 10.1111/febs.13081
|View full text |Cite|
|
Sign up to set email alerts
|

Lithium stimulates human bone marrow derived mesenchymal stem cell proliferation through GSK‐3β‐dependent β‐catenin/Wnt pathway activation

Abstract: Mesenchymal stem cells (MSCs) are multipotent cells that have been widely used in cell based transplantation therapy. The use of MSCs requires in vitro expansion in order to fulfill their regenerative capacity. Therefore the proliferative ability of MSCs is one of the key factors which determine MSC therapeutic efficacy. In the present study, we showed for the first time that lithium, a well-known antidepressant, reversibly promoted the proliferation of human bone marrow derived MSCs in vitro. MSCs treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 79 publications
2
71
0
Order By: Relevance
“…β-catenin accumulation activates transcription in conjunction with co-transcription factors, LEFs/TCFs [32]. It was previously reported that LiCl (5–10 mM) can effectively induce the canonical Wnt signaling pathway and mediate cell differentiation of MSCs [16,17,33] and articular chondrocytes [34]. SB216763 has been shown to regulate cell proliferation and survival and to induce the transcription of β-catenin-dependent genes [24].…”
Section: Discussionmentioning
confidence: 99%
“…β-catenin accumulation activates transcription in conjunction with co-transcription factors, LEFs/TCFs [32]. It was previously reported that LiCl (5–10 mM) can effectively induce the canonical Wnt signaling pathway and mediate cell differentiation of MSCs [16,17,33] and articular chondrocytes [34]. SB216763 has been shown to regulate cell proliferation and survival and to induce the transcription of β-catenin-dependent genes [24].…”
Section: Discussionmentioning
confidence: 99%
“…Han et al [39] showed increase of cell proliferation of human periodontal ligament stem cells (hPDLSCs) up to 5 mM and a decrease at 10 and 20 mM. Zhu et al [40] showed that lithium stimulated proliferation of MSCs up to 5 mM and inhibited at higher concentrations, being able to induce apoptosis above 10 mM. Cell cycle analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In normal cells, on the contrary, both the action of lithium and that of GSK-3β inhibitors has been prevalently linked to an increase rather than a decrease in cell proliferation rates. Examples are neural precursor and mesenchymal stem cells that respond to lithium treatment by undergoing proliferation, typically in a GSK-3β/β-catenin-dependent manner [2,3]. Whether lithium compounds differentially affect the proliferation of normal and cancer SCs remains an open but intriguing question.…”
Section: Discussionmentioning
confidence: 99%
“…Lithium is a well-recognized direct inhibitor of the kinase activity of glycogen synthase kinase (GSK)-3β [1], which is a downstream effector within the signaling network driven by phosphatidylinositol-3-kinase (PI3-K) and protein kinase B or Akt. The interaction of lithium with these ubiquitous pathways has provided a molecular basis for its widespread role in stem cell lineage specification [2], proliferation [3] and differentiation in a variety of cell types [4,5]. …”
Section: Introductionmentioning
confidence: 99%